Role of Complement Receptors (CRs) on DCs in Anti-HIV-1 Immunity - Posch, Wilfried; Bermejo-Jambrina, Marta; Lass-Flörl, Cornelia; Wilflingseder, Doris (Frontiers in Immunology, 2020)
Upon entry of human immunodeficiency virus 1 (HIV-1) into the host, innate immune mechanisms are acting as a first line of defense, that considerably also modify adaptive immunity by the provision of specific signals. Innate and adaptive immune responses are intimately linked and dendritic cells (DCs) together with complement (C) play an important role in regulation of adaptive immunity. Initially, the role of complement was considered to primarily support – or COMPLEMENT - cytolytic actions of antibodies or antibody-complexed antigens (immune complexes, ICs) or directly kill the pathogens by complement-mediated lysis. Recently, the role of complement was revised and found to significantly augmenting and modulating adaptive immunity, in particular against viruses. Complement and DCs are therefore predestined to open novel avenues for antiviral research and potential therapeutic interventions. Recent studies on interactions of complement-opsonized HIV-1 with DCs demonstrated a high potential of such primed DCs to initiate efficient antiviral and cytotoxic anti-HIV-1 immunity and complement-coated viral particles shift DCs functions via CR3 and CR4 in an antithetic manner. This review will focus on our current knowledge of CR3 and CR4 actions on DCs during HIV-1 binding and the outcome of infection influenced by entry and signaling pathways.